IMPROVING FINANCIAL CONTROL AND INTERNAL AUDIT SERVICES IN BUDGET ORGANIZATIONS (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article explores the modernization and enhancement of financial control and internal audit mechanisms within budget organizations. As fiscal transparency and accountability become increasingly essential in public sector governance, the effectiveness of internal audit functions and financial control systems directly impacts the efficiency of budget execution and the prevention of financial mismanagement. The study analyzes current challenges in Uzbekistan’s public financial management system, including fragmented audit practices, limited risk-based auditing, and insufficient institutional capacity. It also reviews international best practices and highlights strategies such as the integration of digital audit tools, capacity building, and regulatory alignment. The paper concludes with recommendations aimed at strengthening the internal control environment and optimizing the role of internal audit in ensuring financial discipline and public sector integrity.